(untitled) (Stamford Journal of English, 2013)
Since Communicative Language Teaching has been introduced in the English classrooms of Bangladesh, we have experienced many changes. As Communicative Approach is supposed to create environment to lessen anxiety and other affective states of learners to a considerable extent, we naturally expected to find students free of the influence of these affective states in tertiary level classrooms. But the real fact is, still a large number of tertiary level second language learners in Bangladesh react to the learning situations in different affective ways. The influence of these affective states on learners’ ability to concentrate on learning is immense. This article intends to analyze the multifaceted and complex nature of learners’ affective states in tertiary level second language classrooms in a private university of Bangladesh and the effects these have on learners’ ability to capture input and produce output or performance. 60 major and non-major English students were selected from a leading private university of Dhaka, who had completed a questionnaire, consisting of 25 questions. The study shows that, affective states play a very strong role in L2 classrooms and most students identify the need to be stress-free and secure before they concentrate on their learning activities. The study also reveals that, speaking and listening are the skills mostly affected by the influence of affective states. Finally, this paper endeavours to offer some recommendations which I found useful in this context, to lessen or eliminate the harmful influence of learners’ affective states on their second language learning. In my paper, I have taken into consideration the students dealing with the four major skills, namely, reading, writing, speaking and listening, as these are the most practiced skills in tertiary level classrooms in Bangladesh. My recommendations 316 will cover practices to be undertaken by both teachers and students, to eliminate or lessen the harmful influence of affective states on learners’ concentration level and performance. Stamford Journal of English; Volume 6; Page 315-331 DOI: http://dx.doi.org/10.3329/sje.v6i0.13920